Web-Based Company Profile Information System Design for SD Negeri 2 Bugis - Agung Priatin; Asep Arwan Sulaeman; Sifa Fauziah (Sean Institute, 2026)
The development of information and digital technology today has a significant impact on information dissemination and institutional image building, including in the field of education. SD Negeri 2 Bugis, as one of the public elementary schools, does not yet have a digital platform that can be used to introduce the school’s profile widely and professionally. To address this issue, this study aims to design a web-based company profile website that facilitates the dissemination of information related to the school’s profile, vision and mission, facilities, learning activities, and achievements of students and teachers. The website is designed with main features such as a school profile page, photo gallery, academic information, and an easily accessible contact page. The results show that the website successfully presents the school’s identity in a professional and interactive manner. With this website, SD Negeri 2 Bugis is expected to enhance its institutional image, improve information accessibility for the community, and reach prospective students more widely in the current digital era.